Effect of lysine modification on the conformational stability of a-Amylase / Tan Cheau Yuaan - Tan, Cheau Yuaan (2011)
Chemical modifications of Bacillus licheniformis –amylase (BLA) were carried out using 100 molar excess of succinic anhydride over protein, 0.66 M potassium cyanate and 0.46 M O-methylisourea under standard conditions to prepare different modified derivatives. The percentage of modification as determined by TNBSA reaction method was found to be 42% for succinylated (S42), 81% for carbamylated (C81) and 88% for guanidinated (G88) BLA derivatives. These modified preparations were checked for their size and charge homogeneity by gel chromatography on Sephacryl S-200 HR column and polyacrylamide gel electrophoresis. Conformational changes in these preparations were detected by analytical gel chromatography on a calibrated Sephacryl S-200 HR column by determining the Stokes radii of native and modified derivatives. C81 BLA was found to have the highest Stokes radius value followed by S42 and G88 BLAs. Conformational stabilities of native and modified BLA derivatives were investigated by urea denaturation using circular dichroism (CD) spectroscopy. Denaturation profiles showed a decrease in the stability of modified BLAs being more pronounced in C81 BLA. In addition, the effect of calcium on urea and guanidine hydrochloride (GdnHCl) denaturation of native and calcium-depleted enzymes was also analyzed by CD, fluorescence spectroscopy and biological activity. Based on these results, calcium was found to stabilize the enzyme against both urea and GdnHCl denaturations.